The Challenges in Moving from Ageing to Successful Longevity - Kolovou, Genovefa; Barzilai, Nir; Caruso, Calogero; Sikora, Ewa; Capri, Miriam; P. Tzanetakou, Irene; Bilianou, Helen; Avery, Peter; Katsiki, Niki; Panotopoulos, George; Franceschi, Claudio; Benetos, Athanase; et al. (Current Vascular Pharmacology, 2014)
During the last decades survival has significantly improved and centenarians are becoming a fast-growing group of the population. Human life span is mainly dependent on environmental and genetic factors. Favourable modifications of lifestyle factors (e.g. physical activity, diet and not smoking) and healthcare (e.g. effective vascular disease prevention) have also increased human life span. Genetic factors contribute to the variation of human life span by around 25%, which is believed to be more profound after 85 years of age. It is likely that multiple factors influence life span and we need answers to questions such as: 1) What does it take to reach 100?, 2) Do centenarians have better health during their lifespan compared with contemporaries who died at a younger age?, 3) Do centenarians have protective modifications of body composition, fat distribution and energy expenditure, maintain high physical and cognitive function, and sustained engagement in social and productive activities?, 4) Do centenarians have genes which contribute to longevity?, 5) Do centenarians benefit from epigenetic phenomena?, 6) Is it possible to influence the transgenerational epigenetic inheritance (epigenetic memory) which leads to longevity?, 7) Is the influence of nutrigenomics important for longevity?, 8) Do centenarians benefit more from drug treatment, particularly in primary prevention?, and, 9) Are there any potential goals for drug research? Many definitions of successful ageing have been proposed, but at present there is no consensus definition. Such definitions may need to differentiate between “Longevity Syndrome” and “Exceptional Longevity”.
Keywords: longevity syndrome